Assessment of knowledge, attitudes, perception and barriers towards pharmacovigilance activities among community pharmacists and final year pharmacy students in Malaysia - Mahmod Elkalmi, Ramadan Mohamed (2010)
Adverse Drug Reactions (ADRs) are associated with a high rate of morbidity and mortality worldwide. In order to overcome this problem, many countries around the world have established national pharmacovigilance systems. Most of the phannacovigilance system nowadays depends largely on ADR Spontaneous Reporting System (SRS) by healthcare professional such as physicians and pharmacists. Within this context, Malaysia established its pharmacovigilance system in 1987. The Malaysian Adverse Drug Reaction Advisory Committee (MADRAC) was established under the umbrella of Drug Control Authority (DCA) for documenting SRS reports received from healthcare professionals. As with most of the spontaneous ADRs reporting system worldwide, the Malaysian SRS has also been affected by underreporting of ADRs especially by the community pharmacists. Data from MADRAC shows that the ADRs reporting rate by community pharmacists is low compared to their counterparts in the other countries. Furthermore, there are no comprehensive studies conducted to explore the reasons behind under reporting of ADRs among community pharmacists in Malaysia. This thesis aims to explore the knowledge, attitude and perception held by community pharmacists regarding ADR reporting.